LAYANAN PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS ANAK CEREBRAL PALSY DI SEKOLAH PAUD HARSYA CERIA BANDA ACEH - Indah Delima; H,ijriati H,ijriati; Friska Imelza; Yurnadia Yurnadia (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The PAUD Harsya Ceria is a school that provides educational services to children. The school accommodates both children with special needs and those without special needs. There are various types of special needs among the children, while others are considered normal. During our observation, we focused on a single child with cerebral palsy. Therefore, our research aimed to understand how children with cerebral palsy are accommodated at PAUD Harsya Ceria School in Banda Aceh. This study utilized a qualitative descriptive approach, employing observation, interviews, and documentation methods. The results of the research indicate that PAUD Harsya Ceria School has provided excellent services for every child, leading to positive changes in each child with cerebral palsy.